Analisis Sistem Informasi Akuntansi, Kualitas Laporan Keuangan, dan Efektivitas Pengambilan Keputusan terhadap Kinerja UMKM - Hutabarat, Metyria Imelda; Harahap, Subur; Wulandari, Ika; Ervina, Nelly (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Analysis of accounting information systems, the quality of financial reports, and the effectiveness of decision making have a significant role in improving the performance of Micro, Small and Medium Enterprises (MSMEs). This research aims to analyze accounting information systems, the quality of financial reports, and the effectiveness of decision making on the performance of MSMEs in Medan City. This research is descriptive research. This research is classified as quantitative research using data obtained from 100 respondents consisting of MSME units. The data collection stage was carried out using an instrument in the form of a questionnaire. The partial results show that the accounting information system has a positive and significant effect on the performance of MSMEs in Medan City. The accounting information system has a positive and significant effect on the performance of MSMEs in Medan City. Apart from that, the effectiveness of decision making has a positive and significant effect on the performance of MSMEs in Medan City. The adjusted R Square value was proven to be 45.1%. Simultaneous results found that accounting information systems, financial report quality, and decision-making effectiveness have a positive and significant effect on the performance of MSMEs in Medan City.